Detection of some new Trichosporon species from the dystrophied nails of three female members of a family from North Indian State of Jammu and Kashmir. Issue 8 (6th April 2018) - Kotwal, Sandeep; Sumbali, Geeta; Sharma, Supriya; Kaul, Sanjana
Summary: Dermatophytes are considered as the main pathogens responsible for onychomycosis, but recently successive isolations of yeast‐like fungi from the infected nails has led to consider these also as primary agents of nail infections. Trichosporon species which are non‐candidal, basidiomycetous, yeast‐like, anamorphic fungi are commonly isolated from soil but they are also emerging as important etiological agents of onychomycosis. Three species of Trichosporon viz., T. asahii, T. asteroides and T. faecale were isolated from the infected nails of three female members of a family from district Doda of Jammu and Kashmir State. Among the isolated species of Trichosporon, T. asahii was recovered from the nail samples of all the three members, thus confirming its recognition as a main pathogenic species of onychomycosis. So far, there is no report of T. asteroides and T. faecale causing onychomycosis and hence they constitute new additions to the list of onychomycotic fungi. Some of the predisposing factors like low socio‐economic condition, poor hygiene, frequent exposure of finger nails to water and dirt, climatic conditions and nail trauma were observed to be the main causes of nail infection in these patients. However, a link between the pathogenic genus and the genetic makeup of the patients is also probable.